2011
DOI: 10.1007/s00535-011-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

Mucin phenotype and narrow-band imaging with magnifying endoscopy for differentiated-type mucosal gastric cancer

Abstract: The mucin phenotype of differentiated early gastric cancer might be involved in morphogenetic differences between the papillary and pit structures visualized by NBI-ME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Tumors positive for both gastric and intestinal phenotypes were regarded as having a gastrointestinal type (Fig. 1c) [21]. All histological evaluations were based on the consensus of 3 pathologists who participated in the present study (T.S., N.U., and M.E.…”
Section: Methodsmentioning
confidence: 99%
“…Tumors positive for both gastric and intestinal phenotypes were regarded as having a gastrointestinal type (Fig. 1c) [21]. All histological evaluations were based on the consensus of 3 pathologists who participated in the present study (T.S., N.U., and M.E.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have reported that clinical findings vary corresponding to cancer cell differentiation. Kobayashi et al (2011) investigated the phenotype expression in the morphogenetic differences between the FNP and the ILL (CLP in this study). They reported that the ILL (CLP in this study) was associated with the G-type and the FNP was associated with the I-type.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported 16, NBI-ME examinations and recordings of endoscopic findings were undertaken by four highly experienced endoscopists (M. K., S. H., K. M., and M. T.). The structural enhancement level was set at B8 for the NBI mode.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining was carried out as previously described 11 16. Surface differentiation was regarded as positive when Ki-67-positive cells were restricted to the middle or lower layer of the lesion (Fig.…”
Section: Methodsmentioning
confidence: 99%